A Bibliometric Analysis of Publications on Systems Thinking in Chemistry Education using Vosviewer, - Kisworo, Banu; Mudzakir, Ahmad; Liliasari, Liliasari; Permanasari, Anna (JKPK (Jurnal Kimia dan Pendidikan Kimia), 2023)
This study utilizes a bibliometric approach along with computational mapping analysis. This study employs a bibliometric approach, complemented by computational mapping using VOSviewer, to explore systems thinking research in chemistry education. The primary goal is to identify key research themes and trends in this field. The initial step involved searching for articles with keywords like "systems thinking" and "chemistry education" using the Publish or Perish software and Google Scholar database. This yielded 922 articles, which were carefully selected based on specific criteria. The comprehensive analysis included co-authorship, co-citation, co-occurrence, cluster, and content analysis using VOSviewer. The quantitative analysis highlights the significance of publications related to systems thinking in chemistry education and broader educational contexts. Over the past decade, prominent themes emerged, including sustainability education, design thinking, outcomes assessment, critical systems, climate change, and more. Qualitative insights further emphasize the relevance of understanding systems thinking in chemistry education, influencing pedagogical approaches and research initiatives. This research aims to provide valuable insights for researchers, educators, and practitioners in the chemistry education field. This study offers a roadmap for future developments by delineating prevalent themes and trends. Understanding the challenges and opportunities in systems thinking research within chemistry education can contribute to enhancing teaching methods and shaping research agendas. This analysis provides a comprehensive overview of the evolving landscape of systems thinking in chemistry education